EFFECT Of IMPLEMENTING INFORMATION SYSTEMS ACCOUNTING AND CONFORMITY OF TASKS – TECHNOLOGY ON EMPLOYEE PERFORMANCE (STUDY AT BPJS EMPLOYMENT BANDUNG) - Ade Pipit Fatmawati (Universitas Pasundan, 2020)
The study aims to test and analyse how much influence the implementation of accounting information systems and the suitability of technological duties towards employee performance. The samples used in this study were 42 employees of BPJS Employment Bandung. Data collection techniques are conducted by spreading the questionnaire to the respondent according to the prescribed sample. Statistical analyses used in the study were through the validity and reliability test of instruments, classical assumption tests, multiple linear regression analyses, correlation analyses and coefficient of determination testing with the help of IBM SPSS version 22. Hypothesis testing was conducted either partially with the T-Test as well as simultaneously through Test F. The results showed that partial, the magnitude of the implementation of accounting system to the employee's performance of 34.9% while the magnitude of Effect of technological task on the employee's performance of 25.8%. Simultaneously the influence of the implementation of accounting information system and the suitability of the technology task on the employee's performance is 35% while the remainder of 65% is the influence of other factors such as motivation, environment, workload, MA Employee's work satisfaction